The Influence of Trauma on Nakajima Atsushi's Character Development in Bungo Stray Dogs - Afitra Devi (Universitas Negeri Surabaya, 2026)
This study analyzes the representation of trauma in Nakajima Atsushi’s character development in Bungo Stray Dogs using trauma theory proposed by Cathy Caruth. Trauma is understood not merely as a painful event, but as an experience that cannot be fully comprehended at the moment it occurs and later returns through flashbacks and recurring emotional wounds. The findings reveal that Atsushi’s childhood trauma influences his self-perception, relationships with others, and decision-making, although over time he begins to accept his past and gradually develops resilience and deeper self-understanding.